IMPLEMENTASI PEMBELAJARAN MEMBACA BERITA MELALUI PEMODELAN - Ninik Sukaryani (EDU-KATA, 2019)
Type of the research is classroom action research. The subject of this research is the students class XI IPS 1 has 30 students in academic year of 2014/2015 semester 2. Implementation of this research is to do 2 cycles, which consist of four activities, that (a) planning, (b) implementing, (c) observing, (d) reflecting. Based on the result of research, it can be known that: The competency of reading news students class XI IPS 1 Madrasah Aliyah Negeri 1 Bojonegoro is good. Implementation of modeling students class XI IPS 1 Madrasah Aliyah Negeri 1 Bojonegoro is good. Based on the computation of the implementation of modeling to increase the competency of reading news students class XI IPS 1 Madrasah Aliyah Negeri 1 Bojonegoro, the first cycles of mastery learning is 56.67%, while for the second cycle of mastery learning is 80%. From the data, the mastery learning from the first cycle to the second cycle has significant increasing. So, it can be said that the implementation of modeling can increase the competence of reading news.